Th17/Treg Cells and Inflammatory Factors in Patients with Thoracolumbar Kyphosis due to Ankylosing Spondylitis: Changes Before and After Vertebral Column Decancellation and Their Relationship with Sagittal Balance - Wang, Yan; Du, Jin; Wang, Tianhao; Xue, Chao; Zheng, Guoquan (Journal of Medical Biochemistry, 2025)
Objective: This study aimed to explore the impact of Th17/Treg cell imbalance and inflammatory factors (IL-1β, IL-18, and TNF-α) on sagittal balance in patients with thoracolumbar kyphosis due to ankylosing spondylitis (AS) following vertebral column decancellation (VCD). Methods: A total of 134 AS patients undergoing VCD were enrolled and categorized into an imbalance group (46 cases) and a balance group (88 cases), depending on postoperative sagittal balance. Measurements of the Th17/Treg ratio and inflammatory factor levels were conducted at three time points: preoperatively (T0), 24 hours postoperatively (T1), and 4 weeks postoperatively (T2). These data were analyzed alongside sagittal parameters (SVA, PI-LL, and PT) to assess their correlations and predictive potential. Results: At 4 weeks after surgery, the imbalance group showed significantly elevated Th17/Treg ratios and higher levels of IL-1β, IL-18, and TNF-α compared to the balance group (P<0.05). Th17/Treg, IL-1β, IL-18, and TNF-α were positively correlated with SVA, PI-LL, and PT (P<0.05). Notably, the combined assessment of Th17/Treg ratio and inflammatory facto52.17% and specificity of 90.91%. Conclusion: The findings suggest that Th17/Treg imbalance and excessive expression of IL-1β, IL-18, and TNF-α are strongly linked to postoperative sagittal imbalance in AS patients. These biomarkers may serve as valuable early predictors for assessing surgical outcomes.